Methane (CH₄) emissions exceeding the threshold from chilli cultivation mulching practices in Sleman Regency, Indonesia - Aristya Ardhitama; Bayu Dwi Apri Nugroho; Junun Sartohadi; Supari Supari; Reni Kraningtyas; Riana Listanti; Khaeruniah Hikmah Taulani (SAINS TANAH - Journal of Soil Science and Agroclimatology, 2025)
Methane (CH₄) is a potent greenhouse gas contributing to global warming, although there is limited information on its emissions dynamics in dryland horticulture. Chilli cultivation practices comprising fertilization and mulching may influence CH₄ emissions through alterations in soil temperature and moisture. Therefore, this study aimed to evaluate the effect of different mulching practices on CH₄ emissions and determine the threshold for sustainable chilli cultivation in tropical dryland conditions. A field experiment was conducted in Sleman, Indonesia, using a randomized block design with three mulch treatments. These included unmulched treatment (M0), organic mulch (M1), and plastic mulch (M2), each replicated three times. Gas sampling was performed biweekly for 112 days using the closed chamber method. Soil temperature and Volumetric Water Content (VWC) were recorded using in situ sensors. The results showed that mulch treatments significantly influenced CH₄ emissions (p < 0.001). M1 produced the highest average CH₄ flux (0.114 mg m⁻² h⁻¹), followed by M2 (0.043 mg m⁻² h⁻¹) and M0 (0.016 mg m⁻² h⁻¹). All treatments exceeded the calculated CH₄ threshold of 0.145 mg m⁻² h⁻¹ under certain conditions. These results showed the need for careful mulching selection to reduce environmental impact and support the development of CH₄ emissions threshold for sustainable dryland horticulture.